2019
DOI: 10.3233/thc-199004
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of a patent foramen ovale and obstructive sleep apnea may increase the risk of wake-up stroke in young adults

Abstract: BACKGROUND: Patent foramen ovale (PFO) and obstructive sleep apnea (OSA) are independent risk factors for young conscious stroke which may also be concomitant symptoms with it. But there is no sufficient attention on these phenomena. OBJECTIVE: To investigate the relationship between PFO, OSA and young stroke, and to look for proper treatment. METHODS: Three patients with young conscious stroke were reported, each of them was combined with PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These patients with stroke at a relatively young age had PFO and had severe OSA in REM sleep with prominent O 2 desaturation accompanied by heart rate elevation and electroencephalogram (EEG) arousals. Similar findings have been reported in a case series with three young patients with "wakeup" stroke with severe OSA (Man et al, 2019). Since the cases that we have described were seen over a span of several years, we have Spencer grading available in only the more recent cases as seen in patient 2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These patients with stroke at a relatively young age had PFO and had severe OSA in REM sleep with prominent O 2 desaturation accompanied by heart rate elevation and electroencephalogram (EEG) arousals. Similar findings have been reported in a case series with three young patients with "wakeup" stroke with severe OSA (Man et al, 2019). Since the cases that we have described were seen over a span of several years, we have Spencer grading available in only the more recent cases as seen in patient 2.…”
Section: Discussionsupporting
confidence: 85%
“…The degree of desaturation during obstructive apneas tends to increase with those with RTLS compared to those without as seen with greater O 2 desaturation during Valsalva (Beelke et al, 2002;Virani et al, 2020). In a case series, patients with cryptogenic strokes and OSA were found to have severe hypoxemia (Man et al, 2019). It was also found that patients with OSA and PFO had significantly increased estimated pulmonary artery systolic pressure (32 vs. 22 mmHg) during Valsalva (Shanoudy et al, 1998;Beelke et al, 2002Beelke et al, , 2003.…”
Section: Introductionmentioning
confidence: 93%
“…Particularly in CS patients with PFO, elevated BMI and the presence of obstructive sleep apnea (OSA) might play a relevant role. Just recently, the coexistence of PFO and OSA in overweight men was suggested as a risk factor for wake-up stroke (47). Moreover, prolonged OSA episodes promoted RLS occurrence during sleep, which might increase the exposure time for paradoxical embolism (48).…”
Section: Discussionmentioning
confidence: 99%
“…Two articles have been published describing five patients with WUS who had moderate to severe OSA and patent foramen ovale (PFO). 56,57…”
Section: What Predisposes To Stroke In Sleep?mentioning
confidence: 99%